A design of machinery learning activity to develop critical thinking. Issue 3 (July 2022) - Sanchez-Londono, David; Posada-Ceron, Sofia; Barbieri, Giacomo; Rodriguez, Carlos Francisco
In engineering education, it is universally recognized that the development of higher-order thinking skills must be encouraged. On the one hand, the backwards design approach allows for the design of courses or activities focused on learning goals rather than on specific content, establishing basic tools to foster these skills. On the other hand, Bloom's taxonomy allows for the separation of macro learning goals into specific learning objectives and adequate evidence. This work integrates the two approaches for the development of an active learning activity for a design of machinery course. The activity consists of introducing students to the design of mechanisms, is developed following the backwards design process and Bloom's taxonomy of learning objectives, and focuses on both technical skills and critical thinking. After designing and testing the activity, the authors found that it allows the acquisition of technical skills in kinematics and kinetics of mechanisms and provides insights for the development of the main components of critical thinking within the machinery design process.